A prática de ensino religioso não confessional: uma análise da perspectiva e do conteúdo da revista Diálogo à luz do modelo das ciências da religião - Barbosa, Roseane do Socorro Gomes (2013)
In the process of developing Religious Education as a subject, there have been different positions regarding its legitimacy, its application and its contents. Even though Religious Education as a subject receives severe criticism, what is questioned is the confessional model. However, there are different ways to present the content, as seen in Revista Diálogo, which has become a reference in its category, since it defends the legislation that refers to Religious Education in itself. This thesis aims at analyzing how is it that Religious Education presents itself in the content of Revista Diálogo in light of the Religious Studies model, to establish a dialogue with some critics opposed to Religious Education and the magazine, and thereby show that it is possible to study religion in the school environment without the confessional perspective, the main target of criticism. The content of the Religious Education curriculum has undergone significant changes along the way. Among other factors that contributed to this change, one must point to Diálogo, whose approach - unlike what has been said by critics - presents religion in its different aspects, respecting religious pluralism, as it exists in Brazil. Given our main thematic reference, besides several issues of Revista Diálogo in itself, the Brazilian legislation, and theoretical referential from authors such as João Décio Passos, and Sérgio Junqueira, and other such texts complement our work. The analysis of Revista Diálogo shows that its approaches address the issues from the perspective of different areas of knowledge and that the Religious Education therein present is the same as that proposed as a model by the Religious Studies. Thus the dissertation opposes the idea of some critics that Religious Education is always confessional